2006
DOI: 10.1021/bm060786e
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Poly(lactic acid) Stereocomplex Nanofibers

Abstract: The electrospinning of stereocomplex nanofibers of high-molecular-weight poly(L-lactic acid) (PLLA)/poly(D-lactic acid) (PDLA) (PLLA/PDLA = 1:1) was carried out with chloroform as the spinning solvent. The stereocomplex nanofibers with diameters of 830-1400 and 400-970 nm were successfully obtained at voltages of -12 and -25 kV, respectively. Wide-angle X-ray scattering indicated that with an increasing absolute value of voltage from 0 to 25 kV the crystallinity of homo-crystallites composed of either PLLA or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 49 publications
(126 reference statements)
5
154
1
Order By: Relevance
“…4B) induces a decrease of the glass transition temperature from 61 to 57 C. A previous study by Zong et al attributed this behavior to an increase of the surface to volume ratio in electrospun materials having air as a plasticizer. Obviously T c max À T g mid also decreases from 43 C to 30 C. This observation is usual in electrospun fibers [31,32,43] as the orientation of the macromolecules enhances the coldcrystallization which therefore occurs at a lower temperature. In the case of electrospun fibers, Tsuji et al [43] conclude that the crystallization has been frozen by the fast removal of the solvent from the electrospun fibers.…”
Section: Tablementioning
confidence: 84%
See 1 more Smart Citation
“…4B) induces a decrease of the glass transition temperature from 61 to 57 C. A previous study by Zong et al attributed this behavior to an increase of the surface to volume ratio in electrospun materials having air as a plasticizer. Obviously T c max À T g mid also decreases from 43 C to 30 C. This observation is usual in electrospun fibers [31,32,43] as the orientation of the macromolecules enhances the coldcrystallization which therefore occurs at a lower temperature. In the case of electrospun fibers, Tsuji et al [43] conclude that the crystallization has been frozen by the fast removal of the solvent from the electrospun fibers.…”
Section: Tablementioning
confidence: 84%
“…Obviously T c max À T g mid also decreases from 43 C to 30 C. This observation is usual in electrospun fibers [31,32,43] as the orientation of the macromolecules enhances the coldcrystallization which therefore occurs at a lower temperature. In the case of electrospun fibers, Tsuji et al [43] conclude that the crystallization has been frozen by the fast removal of the solvent from the electrospun fibers. Edwards et al [44] and Ma et al [32] even consider that extended polymer chains in electrospun fibers can act as row nuclei during heating just above glass transition.…”
Section: Tablementioning
confidence: 84%
“…The peak area of SC increased and that of HC decreased with the decreasing fiber diameter. Tsuji et al 10 reported that the orientation caused by the high voltage or the electrically induced high extensional force during electrospinning process enhances the formation and growth of SC suppressing the formation of HC. In our study, an additional extensional force was given to the spinline by the rotating target.…”
Section: Thermal Analysesmentioning
confidence: 99%
“…To obtain a final product that is flexible, porous, and able to support cell proliferation, electrospinning is often used to produce PLLA nanofibers. 6,7,11 In this process, a polymer solution is ejected under a high-tension electrical field to enable the formation of mesh with a fiber diameter below the micrometer range. Although this technique is very well adapted to research applications, it is unfortunately timeconsuming and scarcely transferable to industrial applications.…”
Section: Introductionmentioning
confidence: 99%